Effects of Cigarette Smoking on Blood Pressure and Hearing Level of Male Adults of Hyderabad, Sindh, Pakistan - Shaikh, Shakil Ahmed; Memon, Salma Farukh; Laghari, Zulfiqar Ali; Bhatti, Muhammad Ali; Shah, Hanozia; Nizamani, Ghulam Shah (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVE: To assess correlation of cigarette smoking on blood pressure and hearing level and Compare with non-smokers. METHODOLOGY: This Cross-Sectional Comparative Study conducted at the department of ENT Combined Military (CMH) Hospital Hyderabad from July to December 2019; Simple random technique was used for data collection. Simple random sampling is the basic sampling technique where we select a group of subjects (a sample) for study from a larger group (a population). Each individual is chosen entirely by chance and each member of the population has an equal chance of being included in the sample. RESULTS: Out of 359 participants, 163 were smoker while 195 were non-smoker. The mean age of smoker was 28.99±3.374 years and non- smoker was 28.00±4.451 years. No significant difference found in both groups regarding their educational standard (systematic collection and analysis of data related to the field of education). Severity of the hearing loss was significantly associated with cigarette smoking. Increased Systolic and diastolic blood pressure was associated with cigarette smoking. CONCLUSION: The evidence was suggestive of positive correlation of cigarette smoking with increases blood pressure and hearing impairment.